INTERNAL MIGRATION IN CENTRAL ASIA: SOCIAL RISKS (CASE STUDIES OF KAZAKHSTAN, TAJIKISTAN, AND KYRGYZSTAN) - NURTAZINA, Roza; TOKTUSHAKOV, Arman (CENTRAL ASIA AND THE CAUCASUS, 2017)
The article examines the processes of internal migration in the countries of Central Asia (Kazakhstan, Tajikistan, and Kyrgyzstan) and the risks that this phenomenon represents for the societies of those countries. The objectives of the study are the definition of the theoretical concepts of migration, internal migration, and social risks, as well as an analysis of the main social risks in the countries of the region. In the course of the study, the context of internal migration is identified and the likely points of social concern and dissatisfaction of the population—the social risks—are revealed. Also identified are the main social risks of internal migration, including disruption in the balance of the labor market, the growth of conflict-proneness in society, reduction in the tolerance toward migrants, excessive urbanization, the decline of rural areas, increase in crime, lowered birth rates, violations of human rights, deterioration of the environment, weakening of territorial and cultural unity, threats to the security and quality of life of local communities, and civic passivity of the migrants in Kazakhstan, Tajikistan, and Kyrgyzstan. The study explores their causes and connection to the current migration processes.